(untitled) (Faridpur Medical College Journal, 2011)
Laparoscopic cholecystectomy (LC) has become the gold standard for the surgical treatment of gallbladder disease, but conversion to open cholecystectomy and postoperative complications are still inevitable in certain cases. Knowledge of the rate and underlying reasons for conversion and postoperative complications could help surgeons during preoperative assessment and improve the informed consent of patients. We decide to review the rate and causes of conversion and postoperative complications of our LC series. This study included 760 consecutive laparoscopic cholecystectomies from July 2006 to June 2011 at Faridpur Central Hospital and Faridpur Medical College Hospital. All patients had surgery performed by same surgeon. Conversion to open cholecystectomy required in 19 (2.5%) patients. The most common reasons for conversion were severe adhesions at calot’s triangle (6, 0.83%) and acutely inflamed gallbladder (5, 0.66%). The incidence of postoperative complications was 1.58%. The most common complication was wound infection, which was seen in 5 (0.66%) patients followed by biliary leakage in 3 (0.40%) patients. Delayed complications seen in our series is port site incisional hernia (2, 0.26%). LC is the preferred method even in difficult cases. Our study emphasizes that although the rate of conversion to open surgery and complication rate are low in experienced hands, the surgeons should keep a low threshold for conversion to open surgery and it should not be taken as a step in the interest of the patient rather than be looked upon as an insult to the surgeon. Key words: Laparoscopic cholecystectomy (LC); Open cholecystectomy; Conversion; Complications; Calot’s triangle DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9204 FMCJ 2011; 6(2): 74-77